Revaluation of Fixed Assets: Innovative Strategies in Optimizing Value and Economic Lifespan at PT Garuda Indonesia - Dewi Sri Wahyuni; Naila Zahira; Desi Enjel Hasibuan; M. Milwan Zuhri; Henny Andriyani Wirananda; Alistraja Dison Silalahi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the implementation of fixed asset revaluation as an innovative strategy to optimize the value and economic useful life of assets at PT Garuda Indonesia (Persero) Tbk. Revaluation is carried out to align the book value of fixed assets with their fair value amid external dynamics, particularly the COVID-19 crisis. Using a descriptive qualitative approach, this research employs secondary data from the company’s annual reports from 2020 to 2024. The results indicate significant fluctuations in revaluation values, reflecting the company’s strategic response to financial pressures and changes in the business environment. Revaluation has contributed to more relevant financial reporting, improved capital structure, fiscal efficiency, and extended economic life of assets. The policy also reflects compliance with PSAK 16 and forms part of a long-term managerial strategy for recovery and enhanced competitiveness. Thus, fixed asset revaluation is not merely a technical accounting measure but a critical instrument in corporate strategic decision-making.